Age-related immunogenicity and reactogenicity of live oral cholera vaccine CVD 103-HgR in a randomized, controlled clinical trial. Issue 11 (7th March 2019) - McCarty, James M.; Lock, Michael D.; Bennett, Sean; Hunt, Kristin M.; Simon, Jakub K.; Gurwith, Marc
Abstract: Aging is accompanied by a decline in immune function which can lead to decreased responses to vaccines. Attenuated recombinant Vibrio cholerae O1 vaccine strain CVD 103-HgR elicits a rapid serum vibriocidal antibody (SVA) response and protects against cholera diarrhea in volunteer challenge studies but has not been studied in older adults. We evaluated CVD 103-HgR (PXVX0200) in adults age 46–64, compared them to previously studied adults age 18–45, and studied age-related immunogenicity across adults 18–64 years of age. Volunteers were randomized to receive a single dose of 1 × 10 9 CFU of PXVX0200 or placebo. Immunogenicity endpoints included SVA and anti-cholera toxin (CT) antibody levels on days 1, 11, 29, 91 and 181 and lipopolysaccharide (LPS) and CT-specific IgA and IgG memory B cells on days 1, 91 and 181. Safety was assessed by comparing solicited signs and symptoms on days 1–8 and other adverse events through day 181. 2979 volunteers received vaccine, including 291 age 45–64. Day 11 seroconversion occurred in 90.4% of older adults vs 93.5%% of younger adults and met the endpoint of demonstrating non-inferiority between the two groups. Significant increases in LPS-specific IgG and IgA and CT-specific memory IgG memory B cells were seen at days 91 and 181. There appeared to be a continuous age-related decline in SVA seroconversion and geometric mean titers, but not memory B cell responses, across the 18–64 year age range. Most reactogenicity was mild and was more common in the placebo group. PXVX0200 appears safe and immunogenic in older adults. Clinical Trials Registration:clinicaltrials.gov NCT02100631.